АНАЛИЗ ВИЗУАЛЬНОЙ КОММУНИКАЦИИ В УЧЕБНИКАХ ИСТОРИИ В УСЛОВИЯХ РЕКОНСТРУКЦИИ ОБРАЗОВАТЕЛЬНЫХ СИСТЕМ В КРИЗИСНЫХ РЕГИОНАХ (Heritage, 2022)
Speaking about crises and their forecasting is always a thankless task. On the one hand, the researcher will receive a lot of criticism from experts in crisis management, economists and analysts. On the other hand, it will find itself in the crossfire of colleagues from related sciences for appropriating and simplifying theories of social and political crises. The processes of digitalization and the emergence of media didactics have led to qualitative changes in the creation and distribution of textbooks, made school knowledge a favorable environment for the formation of future crises associated with contradictions in the interpretation of historical events, the role and place of the individual in history, the construction of conflicting visual images of countries and peoples. In this regard, studies of the monitoring and prognostic function of textbooks as sources of predicting conflicts acquire a new meaning.
Keywords: cognitive maps, problem definition, articulation, reference points, narrative framework, textbook, quantitative and qualitative methods